The Use of Code-Switching in EFL Classroom Instruction and Interaction - Hajar Munawaroh; Rudi Hartono; Zulfa Sakhiyya (Universitas Negeri Semarang, 2022)
This study investigates code-switching in an EFL online classroom interaction. The research data were gathered by using fieldnotes, questionnaires, and semi-structured interviews on one hundred and twenty students and three English teachers. It demonstrates that both teachers and students code-switched during online English lessons. Tag switching and establishing continuity with the previous speaker were mostly used which reached 38.4%, inter-sentential switching15.5%, and intra-sentential 7.7%. respectively. In terms of the language, the findings show that classroom interaction was dominated by the use of Bahasa Indonesia 74.0%, English 52.8%, and Sundanese 16.5%. Code-switching was effective for teachers and students in EFL learning. It proved to 1) significantly influence students' activeness, 2) encourage and give better feedback to students through alternative reinforcement, and 3) encourage better teachers’ and students’ negotiation. With regard to efficiency, conveying meaning of the materials and bringing the project as well as assignment were essential. Nevertheless, some issues came up as a consequence of the Covid -19 outbreaks. Notably, some factors affecting the results were 1) the internet connection, 2) the students’ attendance, and 3) balance. Those results suggest that the potential next research is more likely to respond to students' need to campaign online learning to be better. Some issues come up as consequent of covid-19 outbreaks. Notably, some factors mentioned: (1) the stable or unstable internet connection, (2) the presence of students, and (3) balance. Those results suggest that the potential next research is more likely to respond students’ need to campaign online learning to be better. Keywords: codeswitching, EFL, online learning interaction and instruction